2021
DOI: 10.1039/d1ta00033k
|View full text |Cite
|
Sign up to set email alerts
|

Review on carbonaceous materials as persulfate activators: structure–performance relationship, mechanism and future perspectives on water treatment

Abstract: Recently carbonaceous materials have attracted increasing attentions in advanced oxidation process (AOPs) due to their capability, adaptability and efficiency in the degradation of organic wastewater contaminants with little or no...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(50 citation statements)
references
References 232 publications
2
42
0
Order By: Relevance
“…Carbon materials as catalysts or adsorbents have been widely used in environmental remediation. 21,159 1 O 2 -Dominated oxidation processes were also reported in carbon/PS catalytic systems. 108,160–169 Yu and co-authors reported the 1 O 2 -dominated degradation process in the sludge-derived carbon/PMS catalytic system that showed excellent performance for BPA degradation.…”
Section: Effects Of Anions On Persulfate-based Aops For Sow Treatmentmentioning
confidence: 95%
See 2 more Smart Citations
“…Carbon materials as catalysts or adsorbents have been widely used in environmental remediation. 21,159 1 O 2 -Dominated oxidation processes were also reported in carbon/PS catalytic systems. 108,160–169 Yu and co-authors reported the 1 O 2 -dominated degradation process in the sludge-derived carbon/PMS catalytic system that showed excellent performance for BPA degradation.…”
Section: Effects Of Anions On Persulfate-based Aops For Sow Treatmentmentioning
confidence: 95%
“…13,21 In the activation processes of persulfates, nonradical ROS such as singlet oxygen ( 1 O 2 ), high-valent metals or electrons can be produced to oxidize the organic pollutants under different conditions. 21,22 Compared to ˙OH/SO 4 ˙ − , nonradical ROS showed not only great selectivity, longer lifetime, and good activity in a wide pH range, but also had resistance to impurities such as halide ions or some other anions in water. 16,23–25 PS-AOPs have become hot topics in the SOW treatment due to the various ROS with great selectivity to organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The innovative carbocatalysis in AOPs signicantly expedites the development of new carbocatalysts and excavation of the underlying mechanisms. Till now, several reviews have been reported to summarize the development of carbocatalysis in wastewater decontamination, 9,[12][13][14] while few focused on the application of carbonaceous materials in catalytic ozonation. Recently, two reviews dedicated to the mechanistic investigations on nanocarbon-based catalytic ozonation.…”
Section: Introductionmentioning
confidence: 99%
“…Among the sulfate radical-based AOPs, PMS oxidants have been actively utilized for in situ subsurface remediation owing to their high solubility and reactivity, decent stability, and sustainability [9][10][11][12][13]. PMS can be activated by external energy (e.g., heat, UV radiation, and ultrasound) [9], chemicals [14][15][16], transition metals [17], and carbonbased catalysts [18,19] to produce free sulfate and/or hydroxyl radicals; these radicals are highly reactive toward most organic compounds such as acids, alcohols, aldehyde, aromatics, amines, ethers, and ketones [20][21][22]. Recent studies have proposed that PMS can independently generate the reactive species such as SO 4…”
Section: Introductionmentioning
confidence: 99%